Windshield glass fragment mimicking a nasal fracture - Martini, Marcelo Zillo; Pardo-Kaba, Shajadi Carlos; Seo, Juliana; Yokoyama, Plinio; Horikawa, Fernando Kendi; Snidei, Iron Ricardo Machado; Shinohara, Elio Hitoshi (ARCHIVES OF HEALTH INVESTIGATION, 2019)
A male patient with facial trauma by road traffic accident arrived in the emergency room and he was assisted by the Trauma and Neurosurgery team. After clinical evaluation a frontal sinus anterior wall fracture plus a nasal fracture were diagnosed. On the primary OMS examination was checked multiple facial lacerations and gross nasal dorsum deviation with pain, nasal airway obstruction and crepitus with clinical diagnosis of a nasal fracture. After radiologic exam a piece of windshield glass that was superimposed on the nasal bones simulating a nasal fracture was visualized. This paper presents clinical data and literature review of foreign body mimicking facial fractures. Descriptors: Road Traffic Accident; Facial Fractures; Windshield Glass. Referências Mazinis E, Lambrianidis T, Margelos J. Detection of a residual foreign body during root canal treatment. J Endod. 2005;31(9):691-93. Gray ST. Windshield safety glass foreign body masquerading as a root fragment. Dentomaxillofac Radiol. 1994;23(1):49-51. Goldstein E, Gottlieb MA. Foreign bodies in the nasal fossae of children. Oral Surg Oral Med Oral Pathol. 1973;36(3):446-47 . Madhere S, Barba CA, Painter RL, Morgan AS. Aspiration of shattered windshield glass after blind nasotracheal intubation in a motor vehicle crash. J Trauma. 1997;43:353-56.